2019
DOI: 10.1002/jgh3.12269
|View full text |Cite
|
Sign up to set email alerts
|

Point‐of‐care gastrointestinal ultrasound in inflammatory bowel disease: An accurate alternative for disease monitoring

Abstract: Background and Aim Point‐of‐care ultrasound (POCUS) is a noninvasive alternative to ileocolonoscopy for monitoring disease activity in inflammatory bowel disease (IBD) but is underutilized in practice. Accuracy data are needed to engender clinician confidence in POCUS and increase uptake. The aim of this study was to evaluate the accuracy of POCUS compared to ileocolonoscopy in detecting active disease and extent in patients with IBD. Methods A prospective, blinded study was performed at a single tertiary cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Shatanantan et al compared POC IUS in 74 IBD patients with ileocolonoscopy in a blinded study, and found high sensitivity and specificity of POC IUS for detection of disease activity in both UC and CD. 22 A third study found also a high correlation for IUS and endoscopic disease activity in CD patients. 45 In our cohort we found similar findings.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Shatanantan et al compared POC IUS in 74 IBD patients with ileocolonoscopy in a blinded study, and found high sensitivity and specificity of POC IUS for detection of disease activity in both UC and CD. 22 A third study found also a high correlation for IUS and endoscopic disease activity in CD patients. 45 In our cohort we found similar findings.…”
Section: Discussionmentioning
confidence: 92%
“…Whereas studies have shown good accuracy and reliability of IUS, there are limited data on the impact of IUS outcomes on daily clinical decision making. 21 , 22 …”
Section: Introductionmentioning
confidence: 99%
“…It showed a 91% sensitivity and 83% specificity for detecting endoscopically active IBD, correlating with a positive predictive value (PPV) of 89%, a negative predictive value (NPV) of 86%, and a kappa coefficient of 0.74 (88%). POCUS-defined disease extent has a 87% sensitivity and 81% specificity, correlating with a PPV of 85% and NPV of 83% and a kappa coefficient of 0.70 (85%) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with inflammatory bowel diseases require frequent follow up to evaluate and adjust medical treatment. GIUS in a point-of-care setting has been shown to be accurate,[ 37 ] and the inclusion of POCUS in the decision-making leads to significant changes in disease management. [ 35 38 39 ] Evidence also suggests that the introduction of POCUS reduces the need for magnetic resonance (MR) enterography and colonoscopy.…”
Section: E Xamination T Echniques and ...mentioning
confidence: 99%